The attitude in personal financial management practices by Felda Global Ventures staff / Muhammad Kamil Hanit - Hanit, Muhammad Kamil (Faculty of Business and Management, Universiti Teknologi MARA, 2015)
According to the topic chosen, the attitude in personal financial management practices among Felda Global Ventures staff, the research is conducted to find result for the finding. Research objectives for this study, to determine the level of attitude of Felda Global Ventures staff toward their personal financial management, to determine whether knowledge influence the attitude of Felda Global Ventures staff in their personal financial management, and to determine whether family member influence the attitude of Felda Global Ventures staff in their personal financial management. The scope of the study is mainly focusing on the factors, which are knowledge and family member and whether the both factors is influence the attitude in personal financial management practices by Felda Global Ventures staff. A set of questionnaire was distributed to the respective respondents. There are 100 set of questionnaire that was distributed to the respondents. Several factors has been discussed in this research are demographic, attitude of Felda Global Venture staff toward their financial management, knowledge influence and family influence. The data is analysed using descriptive analysis, frequency, reliability testing, crosstabs and Pearson correlation of Statiscal package for Social Science (SPSS). The studies shows that the independent variable which are knowledge and family members influence chosen by the researcher for this study have relationship with the attitude of Felda Global Ventures staff in financial planning management. To measure the relationship, the researcher used the pearson correlation.